The Impact of Democracy on Human Development in Pakistan - Zeeshan, Zainab; Saleem, Fariha (Pakistan Journal of Humanities and Social Sciences, 2025)
This research aims to find out how the democracy impacted human development in Pakistan. the relationship has been analyzed by adopting the data of the year 1990-2022. The ranking given by Freedom House was taken as a proxy variable for democracy, while the HDI was the variable that was the dependent variables for human development. In addition, this study also considers some of the most important control variables that include trade openness, the GDP per capita and government spending in an attempt to account for the whole political and economic factors which may cause changes in human development. This research ensures use of reliable econometric approaches in the analysis of the data to ensure high reliability in the results obtained. To determine both the long term and short-term relationship, The Augmented Dickey- Fuller (ADF) unit root test, Auto-regressive Distributed Lag (ARDL), and Error Correction Model (ECM) tests are used in the investigation. In order to add another dimension to the consistency of the results we conduct stability and diagnostic tests including testing for serial correlation, heteroscedasticity, stability and normality. The study contributes to the ongoing debate of how democracy and human development is linked, particularly in developing countries like Pakistan. Although earlier research on the relationship between democracy and human growth has produced conflicting findings, with some indicating a favorable relationship and others pointing to the opposite. The Freedom House rating demonstrates a statistically significant and positive influence on HDI, indicating that greater democratic governance is associated with improved human development outcomes in the country. The analysis of government expenditure and GDP per capita further implies that economic forces and democratic governance boost human growth. Finally, there are Positive effects of trade openness in Pakistan’s case according to the findings. The findings demonstrate how important democratic governance is to promoting human growth.